2021
DOI: 10.1113/ep088770
|View full text |Cite
|
Sign up to set email alerts
|

A milk casein hydrolysate‐derived peptide enhances glucose uptake through the AMP‐activated protein kinase signalling pathway in skeletal muscle cells

Abstract: Improvement of glucose metabolism in the skeletal muscle has a key role in exercise performance and prevention of metabolic diseases. In our previous study, we showed that intake of milk casein hydrolysate improves glucose metabolism in humans, but the mechanism of action was not elucidated. In this study, we aimed to investigate the mechanism of action of milk casein hydrolysate and its derived peptides on glucose uptake and glucose metabolic signalling in cultured skeletal muscle cells. Differentiated C2C12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Various food-derived compounds involving biologically active peptides have displayed physiological functions that are potentially valuable in managing and preventing NIDDM. , Several good candidate antidiabetic food compounds have been described. These include the WH dipeptide that activates peptide/histidine transporter 1 (PHT1)-mediated liver kinase B1 (LKB1)/AMPK/Glut4 translocation, tripeptide IPP that activates LKB1/AMPK/Glut4 translocation, and cereal tripeptides that include IQP, IPQ, VEP, and VPE, which activate insulin-independent AMPK/Glut4 translocation. However, the mechanism by which these peptides activate signaling for Glut4 translocation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Various food-derived compounds involving biologically active peptides have displayed physiological functions that are potentially valuable in managing and preventing NIDDM. , Several good candidate antidiabetic food compounds have been described. These include the WH dipeptide that activates peptide/histidine transporter 1 (PHT1)-mediated liver kinase B1 (LKB1)/AMPK/Glut4 translocation, tripeptide IPP that activates LKB1/AMPK/Glut4 translocation, and cereal tripeptides that include IQP, IPQ, VEP, and VPE, which activate insulin-independent AMPK/Glut4 translocation. However, the mechanism by which these peptides activate signaling for Glut4 translocation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies demonstrated that whey hydrolysate, casein hydrolysate, and BCAA-containing peptides can increase the glucose uptake activity and glycogen synthesis rate in skeletal muscle cells. 32,33 Both plasma glucose and muscle glycogen are important fuels for maintaining muscle activity during exercise. 34 However, the glucose content in H-AXH was the lowest and we hypothesized that the uptake of glucose in muscle cells leads to the decrease in plasma glucose, and relevant mechanisms would be further explored.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Since bioactive peptides were discovered in 1979, different biological activities have been described as antioxidant, antimicrobial, opioid, immunomodulatory, anti-inflammatory, antihypertensive, antidiabetic or hypocholesterolemic, among others (87,88). In this sense, some studies reported that certain bioactive peptides may exert a positive effect on muscle glucose uptake and glycogen restore by activating insulin-independent AMP-activated protein kinase signaling in skeletal muscle cells (89,90). Moreover, endogenous insulin appears to exert a positive effect on MPS due to their vasodilator effect by stimulating endothelial nitric oxide production, and increasing skeletal muscle glucose uptake (91).…”
Section: Hydrolysates and Peptidesmentioning
confidence: 99%